(untitled) (Bangladesh Journal of Botany, 2018)
Drought stress decreased leaf water absorption capacity and real water content and increase relative water content in genotypes of chickpea. It decreased chlorophyll a and b content. Drought increased peroxidase superoxide dismutase, glutathione reductase, ascorbate peroxidase and catalase in stress groups. Proline content increased drastically index stress condition.